Konsep Inteligensi dan Peranan dalam Proses Pembelajaran di Sekolah - Habsy, Bakhrudin All; Pratama, Gadis Putri Amelia; Hakiki, Intan Ainul; Nabella, Kharisma Putri (Lembaga Yasin AlSys, 2024)
The aim of this research is to describe the participants' main ideas about intelligence and explain what roles influence the learning process for students. In this research, researchers used qualitative methods that are literary in nature. The results of this research state that intelligence is very influential in the students' learning process because it can be seen that students who have high intelligence can more easily participate in learning activities quickly and well compared to students who have low intelligence. Suggestions from this research enrich the study of intelligence and its role in the learning process.